Exploring agape: Tourists on the island of love - Christou, Prokopis A. (My University, 2018)
This study explored the extent to which tourists take part in a distinct type of love, agape, which is described as sincere and not selfseeking. Findings from 80 semi-structured interviews in Cyprus reveal that tourists acknowledge the constructive effects of love in general, at a personal and societal level, despite no consensus being reached on the interpretation of the term. Even so, love seems not to be solely the outcome of human transactions. It is also determined by the cultivation of a caring culture towards the facilitative and natural setting in which social dealings take place. Although responses betray the conveyance of offerings that are in line with agape's dogmata, one might argue whether what tourists experience, is agape in its essence. Nonetheless, managerial implications are discussed.
Keywords: Agape; Cyprus; Emotions; Love; Tourist experience